Interim efficacy and safety of PD-1 inhibitors in preventing recurrence of hepatocellular carcinoma after interventional therapy - Qiao, Wenying; Wang, Qi; Hu, Caixia; Zhang, Yinghua; Li, Jianjun; Sun, Yu; Yuan, Chunwang; Wang, Wen; Liu, Biyu; Zhang, Yonghong (Frontiers in Immunology, 2022)
Introduction: Locoregional interventional therapy including transcatheter arterial chemoembolization (TACE) and ablation are the current standard of treatment for early-to-mid-stage hepatocellular carcinoma (HCC). However, questions remain unanswered regarding the management of recurrence after locoregional treatment. PD-1 inhibitors can block inhibitory signals of T-cell activation and proliferation to reduce the recurrence. We conducted a single-arm phase 2 trial to evaluate the efficacy and safety of PD-1 inhibitors following locoregional interventional therapy in HCC patients with high recurrence risk guided by our novel scoring system. Methods: Patients enrolled initially treated by TACE combined with ablation, then willingly joined experimental group. One month later, they received the anti-PD-1 adjuvant therapy (200 mg intravenously), which was repeated every 3 weeks for a total of 4 or 8 cycles. Within this same period, other patients were screened to the control group to match experimental group by 1:1 on the basis of the propensity score matching method (PSM). The primary endpoint was relapse-free survival (RFS). Secondary endpoints included overall survival (OS) recurrence modality, safety, and quality of life. Result：At the time of data cutoff, the median RFS of the control group was 7.0 months while the experimental group had not reached. Moreover, the 1-year RFS rate was 73.3% in the experimental group and 46.7% in the control group, showing a significant difference (P =0.02). The rate of local tumor progression in experimental group was clearly lower than that in control group (P = 0.027). Benefits associated with anti-PD-1 adjuvant therapy were observed in patients with multiple tumors and tumor size ≤2cm. Univariate and multivariate analyses demonstrated that anti-PD-1 adjuvant therapy was an independent favorable prognostic factor for RFS in HCC patients. The most frequent AE observed in this study were RCCEP, and other AEs included diarrhea, hepatotoxicity, rash, pruritus and fatigue. The incidence of GRADE ≥3 AE and withdrawal in this study was low with no deaths were recorded. Conclusions: Interim analysis from the study suggest the addition of anti-PD-1 adjuvant therapy after TACE combined with ablation could significantly prolong RFS with controllable safety for the early-to-mid-stage HCC patients with high recurrence risk.